Integrating the Internet of Things with Enterprise Resource Planning System for Management Educational Institutes - Sangkhapan, Surachet; Nilsook, Prachyanun (Princess of Naradhiwas University Journal, 2019)
In educational ERP has played a key role in the management of the IT systems of higher education, including human resources. Student information systems, financial systems, and technical articles, this study documents and research related to the integration of the Internet of Things to an enterprise resource management system for educational purposes of this article, the main issue is the concept of integration. Internet of things technology, and enterprise resource management system for school administrators. The study began by studying documents and related research, analysis, and synthesis. The author is presented in context 1) Enterprise Resource Planning systems (Enterprise Resource Planning System: ERPs) 2) the composition of the ERP in an organization 3) Cloud ERP systems in the enterprise, 4) integration of ERP to the administrators. 5) factors related to ERP 6) accepted the use of ERP 7) IoT: Internet of Things 8) Outlook integration IoT with the ERP In addition, the need for further study on the factors that lead to the adoption and application of technology to maximize the benefits in further studies.